Pendampingan Pengolahan Kompos Berbasis Bioaktivator Mikroorganisme Selulolitik Bagi Kelompok Wanita Tani (KWT) Bungoeng Jeumpa Desa Lapang Aceh Barat - Dewi Junita; Agustinur Agustinur; Sumeinika Fitria Lizmah; Muhammad Afrillah; Nana Ariska; Chairul Rizal (Jurnal Pengabdian UNDIKMA, 2023)
This Service community aims to improve the comprehension and skills of KWT Bungoeng Jeumpa members about the processing organic waste into compost based on cellulolytic microorganism bioactivators regarding the processing of organic waste into bioactivator-based compost to fulfill fertilizer needs in KWT Bungoeng Jeumpa. The methods of this service were counseling and practice, which consisted of the initial stage (preparation, survey, and focus group discussion), the implementation stage (Counseling and practice), and the evaluation at final stage. The target partners for this service activity were KWT, totaling 21 members. The instrument for evaluating this activity used a questionnaire and were analyzed descriptively. The results of this community service activity showed that the understanding and skills of KWT Bungoeng Jeumpa members increased regarding compost processing based on microorganism bioactivators, following the results of the evaluation where the understanding and abilities of KWT Bungoeng Jeumpa members increased by 28.57% and 14.25%.